Paradigma Teo-Antroposentris dalam Interpretasi Hadis: Analisis Tematik atas Riwayat Muslim tentang Perkataan Baik - Lestari Lestari; Qur’ani Parang Wilwadikta; Abu Samsudin (Institut Agama Islam Negeri Kediri, 2026)
Studies on hadiths concerning speech ethics have largely been confined to normative explanations or partial social applications, leaving the relationship between divine orientation and human responsibility insufficiently explored within an integrative interpretive framework. The hadith encouraging believers to “speak good or remain silent” reflects a close interconnection between faith and communicative ethics in social life. This study examines a hadith narrated by Muslim through a theo-anthropocentric paradigm to elucidate the interplay between divine values and human dimensions in the construction of hadith meaning. Employing a qualitative library-based method, the study applies a thematic-analytical approach to the hadith text, classical commentaries, and relevant contemporary scholarship. The findings demonstrate that the hadith functions not merely as a spiritual injunction concerning restraint of speech as an expression of faith, but also as a foundation for social ethics oriented toward preventing harm, fostering respect for others, and maintaining social harmony. Within the theo-anthropocentric framework, silence is understood as a preventive ethical act aimed at avoiding moral damage caused by irresponsible communication. This study contributes to the development of an interpretive framework for ethical hadiths that contextually integrates the normative authority of revelation with social reality.